Calcium Phosphate Bone Cement Prepared Using Wet Precipitation Method at Powder-to-Liquid Ratios of 1.3 and 1.7 - Hablee, Sufiamie; Sopyan, Iis; Mel, Maizirwan; Mohd. Salleh, Hamzah; Mujibur Rahman, Md.; Singh, Ramesh (International Journal of Engineering and Technology, 2018)
Calcium phosphate/poly(ethylene glycol) composite for bone cement use has been developed by incorporating poly(ethylene glycol) (PEG) into calcium phosphate cement (CPC) prepared using wet chemical precipitation method with the powder-to-liquid (P/L) ratios of 1.3 and 1.7. The precursors used in the synthesis are calcium hydroxide, Ca(OH)2, and diammonium hydrogen phosphate, (NH4)2HPO4. The effect of PEG addition on injectability, setting behaviour, mechanical properties and anti-washout performance of CPC was investigated. The results indicated that PEG addition significantly improved setting time, injectability, compressive strength as well as anti-washout performance of CPC. The initial and final setting times of PEG free CPC with the P/L ratio of 1.3 are 88 min and 228 min, respectively. The addition of 4% PEG shortened both the initial and final settimg times to 47 min and 182 min, respectively. Without PEG, CPC with the P/L ratio of 1.7 has the compressive strength of 0.25 MPa. The compressive strength increased to 1.553 MPa when 5% PEG was added. The anti-washout properties of CPC/PEG is excellent with no cement dissolution throughout 28 days soaking period.Â Â